Analysis of Current Drug Situation Problem - Jandeang, Burachat (Journal for Developing the Social and Community, 2017)
The current situation has been spreading drug abuse which widespread and more severe, it cause loss to the nation, people, economic, social and political dominance together. Government still aware of this problems by setting the priority to reduce outbreaks and tackle drugs. However, the strategies for participating in share issue related to spread of drugs in country including legal measures to resolutely those guilty of drug trafficking and drug abuse